ANALYSIS OF MULTIPLE REPRESENTATION ABILITIES OF MALE AND FEMALE GRADE STUDENT AT SMAN 1 TANJUNGANOM IN ACID-BASE MATERIAL - Hidayah, Rahayu Nur; Ardhana, Ivan Ashif (Universitas Negeri Surabaya, 2024)
The field of chemistry has become one of the abstract sciences, particularly in the context of acid-base materials, thus requiring the integration of multiple representations. Incomplete multiple representation abilities in students can lead to difficulties in understanding acid-base materials. Therefore, this research aims to analyze (1) the level of students' multiple representation abilities in acid-base materials and (2) the differences in the levels of multiple representation abilities between male and female students. The research method used is a comparative ex-post facto approach with a quantitative approach. The research instruments include test questions based on the DAC framework and interview sheets. The results of this research are as follows: (1) the average level of multiple representation abilities is 20%, categorized as very poor. The percentages of multiple representation abilities based on the DAC framework are 29% for definition, 18% for algorithmic, and 20% for conceptual. The highest percentage in the DAC framework indicators is D-R at 32%, while the lowest percentage is C-O at 11%. (2) There is a difference in the levels of multiple representation abilities between male and female students, as evidenced by the results of the Mann-Whitney U test, with an Asymp. Sig. (2-tailed) value of 0.000 ≤ 0.05.